A real-world analysis of second-line treatment options in pancreatic cancer: liposomal-irinotecan plus 5-fluorouracil and folinic acid. (July 2019) - Kieler, Markus; Unseld, Matthias; Bianconi, Daniela; Scheithauer, Werner; Prager, Gerald W.
Background: Nanoliposomal irinotecan (nal-IRI) plus 5-fluorouracil/leucovorin (5-FU/LV) is a novel treatment option for gemcitabine-pretreated metastatic pancreatic adenocarcinoma (PAC) patients, but real-world evidence is rare. Our aim was to determine the effectiveness and tolerability of this regimen in advanced PAC patients and to compare it with oxaliplatin plus fluoropyrimidines in the second-line setting after failure of gemcitabine. Methods: This is a retrospective single-center analysis of all patients who have been treated with nal-IRI plus 5-FU/LV. To compare its effectiveness with other second-line treatment options, all patients who had received oxaliplatin plus fluoropyrimidines after gemcitabine-based chemotherapy were also eligible for analysis. Results: Fifty-two patients were treated with nal-IRI plus 5-FU/LV between April 2016 and August 2018. The median progression-free survival (PFS) was 3.84 months and the median overall survival (OS) was 6.79 months. Median OS from the beginning of the treatment for advanced disease was 19.9 months. Median PFS in patients that received nal-IRI plus 5-FU/LV as second-line treatment after gemcitabine-based chemotherapy was 4.49 months whereas median PFS in a matched cohort of patients treated with oxaliplatin plus fluoropyrimidines was 3.44 months ( p = 0.007). Between these two groups the median OS of patients with CA 19-9 levels above the statistical median (⩾772.8 kU/l) differed significantly (9.33 versus 6.18 months, p = 0.038). Conclusion: Our data confirms the effectiveness of nal-IRI plus 5-FU/LV treatment as a well-tolerated regimen in the treatment of advanced PAC and extends available data on its use as a second-line treatment option when compared with oxaliplatin plus fluoropyrimidines.